TANAMAN KELOR SEBAGAI PELENGKAP PANGAN DAN NILAI EKONOMIS PADA MASYARAKAT DESA TISTA, KECAMATAN ABANG KABUPATEN KARANGASEM - I Made Suasti Puja (UNHI Press, 2021)
The covid 19 pandemic has lasted almost 1 year 7 months from all over Indonesia, the most prominent in the economy is Bali island, because there are no foreign & domestic guests, that cause tourism sector. The economic contraction caused many people who work in that sector are lose their jobs and to survive they return to their home town to work as farmers. The covid-19 pandemic has not slowed yet the government to implement the Implementation of Community Activity Restrictions (PPKM). During the PPKM in Bali, the Universitas Hindu Indonesia (UNHI) have to carry out the Tri Dharma Perguruan Tinggi by carrying out the Community Service Program (KKN) the Thematic of the Universitas Hindu Indonesia with theme